Can the right hemisphere read? A behavioral and disconnectome study on implicit reading in a patient with pure alexia. Issue 6 (1st November 2020) - Bonandrini, Rolando; Veronelli, Laura; Licciardo, Daniele; Caporali, Alessandra; Judica, Elda; Corbo, Massimo; Luzzatti, Claudio
ABSTRACT: Patients with pure alexia have major difficulties in reading aloud. However, they often perform above chance level in reading tasks that do not require overt articulation of the target word – like lexical decision or semantic judgment – a phenomenon usually known as "implicit reading." There is no agreement in the literature on whether implicit reading should be attributed to relative sparing of some left hemisphere (LH) reading centers or rather to signs of compensatory endeavors by the right hemisphere (RH). We report the case of an 81-year-old patient (AA) with pure alexia due to a lesion involving the left occipital lobe and the temporal infero-mesial areas, as well as the posterior callosal pathways. Although AA's reading was severely impaired and proceeded letter by letter, she showed an above-chance-level performance for frequent concrete words in a tachistoscopic lexical decision task. A structural disconnectome analysis revealed that AA's lesion not only affected the left occipital cortex and the splenium: it also disconnected white-matter tracts meant to connect the visual word-form system to decision-related frontal areas within the LH. We suggest that the RH, rather than the LH, may be responsible for patient AA's implicit reading.